Genomic Analyses of Metaplastic or Sarcomatoid Carcinomas From Different Organs Revealed Frequent Mutations in KMT2D - Zheng, Biqiang; Song, Zhijian; Chen, Yong; Yan, Wangjun (Frontiers in Molecular Biosciences, 2021)
BACKGROUND: Metaplastic or sarcomatoid carcinomas (MSCs) are rare epithelial malignancies with heterologous histological differentiation that can occur in different organs. The objective of the current study was to identify novel somatically mutated genes in MSCs from different organs. METHODS: Whole-exome sequencing was performed in 16 paired MSCs originating from the breast (n=10), esophagus (n=3), lung (n=2), and kidney (n=1). In addition, we collected data on KMT2D mutations from 8 independent cohorts (n=195) diagnosed with MSCs derived from the breast (n=83), liver (n=8), esophagus (n=15), lung (n=10), and uterus or ovary (n=79). The expression of KMT2D and its clinical significance were evaluated in our cohort. RESULTS: The most frequently mutated genes were TP53 (13/16, 81%) and KMT2D (5/16,31%). We identified 7 somatic KMT2D mutations in the exploratory cohort (n = 16 tumors), including 3 nonsense mutations, 2 frameshift indels, 1 missense mutation, and 1 splice site mutation. Interestingly, 2 patients showed double hits on KMT2D with nonsense mutations and frameshift indels. In the 8 validation cohorts (n=195), the average mutation rates for TP53 and KMT2D were 78% (152/195) and 13% (25/195), respectively. Two or more hits on KMT2D were also present in three validation cohorts. Furthermore, KMT2D mutations were associated with low expression of KMT2D, large tumor size and unfavorable prognosis. CONCLUSIONS: These findings provide clues for understanding the genetic basis of MSCs originating from different organs and implicate KMT2D alteration as a frequent pathogenic mutation, allowing provision of appropriate treatment for this rare malignant disease in the future.